Solving the Phase Dispersion Issue in FMCW Photonic Time Multiplexed Radar Imaging - Berland, Fabien; Elwan, Hamza Hallak; Boudescoque, Damien; Decroze, Cyril; Di Bin, Philippe; Aupetit-Berthelemot, Christelle; Fromenteze, Thomas (2021 15th European Conference on Antennas and Propagation (EuCAP), 2021)
The frequency-modulated continuous-wave architectures are increasingly used in 3D imaging systems to reduce the constraints linked to the receptive components. For short-range applications, the phase dispersion term that appears when de-chirping these signals is generally considered negligible due to the relatively low propagation delays. However, in this paper, the frequency-modulated continuous-wave architecture is implemented into a short-range radio frequency imaging system which uses a time-division multiplexer in reception. Under these conditions, even if the scanned scene range is small, the received signals are subject to significant delays and the undesirable phase dispersion term becomes non-negligible. Its impact on the reconstructed image is studied here using simulations that consider different delay for the multiplexing and using the measurement of a scene with a multiple-input multiple-output antenna array.